GEANT4 tuning for pCT development - Yevseyeva, Olga; De Assis, Joaquim T.; Evseev, Ivan; Schelin, Hugo R.; Paschuk, Sergei A.; Milhoretto, Edney; Setti, João A. P.; Díaz, Katherin S.; Hormaza, Joel M. [UNESP]; Lopes, Ricardo T. (AIP Publishing, 2011)
Proton beams in medical applications deal with relatively thick targets like the human head or trunk. Thus, the fidelity of proton computed tomography (pCT) simulations as a tool for proton therapy planning depends in the general case on the accuracy of results obtained for the proton interaction with thick absorbers. GEANT4 simulations of proton energy spectra after passing thick absorbers do not agree well with existing experimental data, as showed previously. Moreover, the spectra simulated for the Bethe-Bloch domain showed an unexpected sensitivity to the choice of low-energy electromagnetic models during the code execution. These observations were done with the GEANT4 version 8.2 during our simulations for pCT. This work describes in more details the simulations of the proton passage through aluminum absorbers with varied thickness. The simulations were done by modifying only the geometry in the Hadrontherapy Example, and for all available choices of the Electromagnetic Physics Models. As the most probable reasons for these effects is some specific feature in the code, or some specific implicit parameters in the GEANT4 manual, we continued our study with version 9.2 of the code. Some improvements in comparison with our previous results were obtained. The simulations were performed considering further applications for pCT development. © 2011 American Institute of Physics.
Keywords: GEANT4 code; Monte Carlo simulations; Proton computed tomography (pCT)